Strategi inovatif perbankan syariah di era digital: Membangun keunggulan kompetitif - Hariyono, Bunga Prameswari (Maliki Interdisciplinary Journal, 2025)
The digital era has transformed the landscape of the banking industry, including Islamic banking, which is now required to adopt technology as part of innovative strategies to face global competition. This article discusses various innovative strategies that Islamic banks can implement to build competitive advantages, enhance services, and expand customer outreach. By leveraging digital technologies such as mobile banking, big data, and artificial intelligence, Islamic banks can improve operational efficiency and enhance customer experiences. Moreover, the development of innovative Sharia-compliant products and services plays a crucial role in attracting a broader market segment, particularly the tech-savvy younger generation. This study also highlights the importance of balancing technology adoption with Sharia principles, ensuring that innovations remain aligned with Islamic values. Consequently, innovative strategies in the digital era will be key to strengthening the competitiveness of Islamic banking in the modern financial market.